15. STUDY ON FERRITIN CONCENTRATION AND RELATIONSHIP WITH SOME CLINICAL INDICATORS IN COVID-19 PATIENTS (Vietnam Journal of Community Medicine, 2024)
Objective: Determine ferritin concentration according to disease severity and relationship with some clinical indicators in COVID-19 patients. Subject and method: From February 2022 - April 2023; at the Department of Biochemistry, Covid Center - Military Hospital 103; Cross-sectional description study method using forf 155 COVID-19 patients (50 mild patients, 70 moderate patients, 35 severe patients) who fully met research criteria. Results: Ferritin concentration in study subjects with mild disease was 293.45 ng/ml, average level was 421.19 ng/ml, severe level was 794.35 ng/ml, differences between disease levels were significant. statistical significance with p < 0.001; The proportion of patients with increased ferritin compared to the reference value (0-300 ng/mL) gradually increases with disease severity (mild severity group is 44%, moderate severity group is 61.43%, severe severity group is 77.14 %), ferritin concentration is related to disease severity with p < 0.05; The ferritin threshold that differentiates mild-moderate patients is 150.6 ng/mL (AUC = 0.678) and the ferritin threshold that differentiates severe patients is 446.08 ng/mL (AUC = 0.668); Ferritin concentration has a moderate positive relationship with age (r = 0.308, p < 0.05), gender (r = 0.352, p = 0.000) and disease severity (r = 0.352, p = 0.000); In the severe group, Ferritin concentration had a moderate positive relationship with breathing frequency (r = 0.367, p = 0.03), with no relationship with SpO2. Conclusion: Ferritin concentrations in research subjects gradually increased and were related to disease severity; Ferritin concentration has a moderate positive relationship with age, gender and disease severity; Ferritin concentration has a moderate positive relationship with breathing frequency in the severe group.
Keywords: Ferritin, Covid-19.